العمل التطوعي للمرأة وأثره على تمكينها الاجتماعي - حباس, أسية (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى فهم العلاقة القائمة بين العمل التطوعي وتمكين المرأة، من خلال تحليل الكيفية التي يساهم بها هذا النشاط في بناء كفاءاتها وتطوير مهاراتها المهنية والاجتماعية، وتعزيز فرص اندماجها في سوق العمل، وذلك عن طريق تحليل تجارب النساء داخل الأطر التطوعية، باعتبارها مواقع ديناميكية تؤثر في مسارات التمكين والتحول الاجتماعي والمهني. ولتحقيق ذلك، تم اعتماد المنهج الكيفي باستخدام أداة المقابلة نصف الموجهة، حيث أُجريت مع عينة مكوّنة من عشرين امرأة منخرطة في العمل التطوعي، تم اختيارهن بطريقة "كرة الثلج". وقد بينت النتائج أن العمل التطوعي يُعد فضاءً مزدوج الفائدة بالنسبة للمرأة، فهو يعزز تمكينها الاجتماعي، وفي الوقت نفسه يشكل وسيلة فعالة لاكتساب الكفاءات المهنية التي تؤهلها للاندماج في سوق العمل. كما أظهرت الدراسة أن الجمعيات والمساجد مثلت فضاءات حاضنة للتدريب والتكوين، حيث استفادت المرأة من دورات تكوينية وممارسات تطبيقية مكّنتها من إثبات ذاتها واكتشاف قدراتها داخل محيطها الاجتماعي والمهني. This study aims to understand the relationship between volunteer work and women's empowerment by analyzing how this activity contributes to building their competencies, developing their professional and social skills, and enhancing their chances of integration into the labor market. This is achieved by examining the experiences of women within voluntary frameworks, considered as dynamic spaces influencing pathways of empowerment and both social and professional transformation. To achieve this, a qualitative approach was adopted using the semi-structured interview tool, conducted with a sample of twenty women engaged in volunteer work, selected through the "snowball" technique. The results revealed that volunteer work constitutes a dual-benefit environment for women: it enhances their social empowerment while also serving as an effective means to acquire professional competencies that facilitate their integration into the job market. The study also showed that associations and mosques acted as supportive environments for training and capacity-building, where women benefited from training sessions and practical experiences that enabled them to assert themselves and discover their capabilities within their social and professional surroundings.
دراسة ميدانية في ولاية مستغانم لدى النساء المتطوعات
Keywords: العمل التطوعي للمرأة، التمكين الاجتماعي، الكفاءة المهنية، الاندماج المهني